Adaptasi Alat Ukur Stres Berkendara bagi Pengendara Motor di Indonesia - Novika Grasiaswaty; Alexandra Aliviary; Nuri Sadida (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
The driving stress scale is one of the stress measuring tools for car drivers and so far, the Indonesian version of the measuring instrument has not been found. Adaptation of this measuring tool is needed considering that the construct has been more suitable for car drivers, while for motorcycle riders, adaptation is needed, especially in Indonesia. The adaptation of measuring instruments using driving stress consists of 16 items and is a unidimensional measuring instrument. The adaptation process follows six stages (translate-synthesis-backwards translate), both qualitative and quantitative. The results of the measurement tool translation were then given to eight online motorcycle taxi drivers and they were asked to read each item to check understanding in each item. Based on the qualitative process, some words were changed. The DS-Indonesia version was then returned to three online motorcycle taxi drivers to be re-tested for readability. These results were then tested (try out) to 28 online motorcycle taxi drivers to be analyzed quantitatively. Improvements were made again so that there were some item changes. The final result of this item was then collected data on 200 online motorcycle taxi drivers. Reliability testing and Confirmatory Factor Analysis with the R platform and Lavaan packages were used to check the suitability of each item with the DS-Indonesia unidimensional factor. It is known if the value of x2 : 57.114 p0.001, CFI = 0.969; TLI = 0.906 . RMSEA =0.078; SRMR = 0.040 which indicates that the results of the DS-Indonesia adaptation data have a fairly good fitness value. The inter-item results are in the good range and the correlation with BFI-Indonesia shows that DS-Indonesia correlates with the neuroticism, consciousness, agreeableness and openness traits but not with extraversion.